eview of the future of ecology education (2014)
This paper emphasizes the future of ecology education. It defines education as a process and procedure of imparting and acquiring of knowledge through teaching and learning, especially at a school or similar institution and environment. The paper asserts that a right to education has been recognized by some governments since at the global level, Article 13 of the United Nations' 1966 International Convention on Economic, Social and Cultural Rights recognizes the right of everyone to an education. Although education is compulsory in most places up to a certain age, attendance at school often isn't, and a minority of parents often choose home-schooling, e-learning or similar for their children. The history and current state of ecology education is reviewed. The paper concludes that the challenge of funding would continue to reverberate in educational circles as more support systems and endowments are sought and found.vvv